Developing Sukuk Parameters from Maqasid Al-Shari’ah of Wealth: Contextualising from The Perspective of Selected Contemporary Islamic Scholars - Melzatia Shinta; R. B. Radin Firdaus; Sorna Umme Saima; Andrew Ebekozien (Journal of Islamic Finance, 2023)
Sukuk is an emerging instrument that matches savers and investors in the capital market. Over the years, Sukuk operations in the capital market worldwide have been subject to criticism because of their impotence to fully adopt Shari’ah principles. Establishing a Sukuk parameter could be the key to aligning Sukuk with Shari’ah principles, where the Maqasid al-Shari’ah of wealth could serve as a basis for developing the parameter. As such, this study identifies the wealth perspectives of Maqasid al-Shari’ah and contextualises the dimension of wealth according to Maqasid al-Shari’ah based on the perspective of renowned contemporary Islamic scholars. Using Maqasid al-Shari’ah of wealth as an underpinning framework, this study proposes a baseline for the Sukuk parameter. The finding suggests that the Sukuk parameters must be formulated based on the Maqasid al-Shari’ah of wealth (adequate level as an ideal level in wealth ownership). Apart from Maqasid al-Shari’ah of wealth ownership, the parameter encompasses Maqasid al-Shari’ah of wealth acquisition and Maqasid al-Shari’ah of wealth circulation/development. As part of the implications, the proposed parameters would provide a baseline for establishing the Sukuk parameter. This study implies that contextualising Sukuk and its issuance using the Maqasid al-Shari’ah approach would enable Sukuk to achieve its ultimate objective of promoting Maslahah (well-being).